Motivasi Orangtua Memilih Sekolah Bilingual untuk Anak Usia Dini - Winarti Agustina (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2020)
This study aims to describe the aspects that cause parents to get motivated in choosing bilingual kindergarten for their children in Bekasi and to find out which aspects are dominant. This descriptive research used a quantitative research method. The research method used in this study is conducted through a survey. 205 parents with children up to six years old (early childhood) in Bekasi are the subjects of this study. Data collection techniques are implemented using multilevel scale questionnaire. The results appeared that what makes parents get motivated in choosing bilingual school for their children are derived from internal and external motivation. Internal motivation consists of (1) aspects of needs and (2) aspects of hope, while external motivation includes (3) aspects of child’s talents and interests, (4) aspects of psychology, (5) aspects of friends, (6) aspects of facilities and infrastructure, and (7) aspects of teachers. The results are based on average differences in the questionnaire from seven aspects with the breakdown: aspects of needs for 3.40, aspects of hope for 3.39, aspects of child’s talents and interests for 3.22, aspects of psychology for 3.20, aspects of friends for 3.42, aspects of facilities and infrastructure for 3.22, and aspects of teachers for 3.24. Descriptively, the aspects that influence parents in choosing bilingual school are aspects of friends. The seven aspects were tested by Tukey’s HSD to analyze the variety by comparing these seven aspects and seeing the average similarity. Thus, the motivation variable significantly influences the differences in the aspects of psychology, children's talents and interests, facilities and infrastructure, and teachers with the aspects of hopes, needs, and friends